The Impact of PjBL-STEM Integrated EDP Strategy with Deep Learning to Improve Creative Problem-Solving Skills - Dwi Wulandari; Abdurrahman Abdurrahman; Blasius Anggit Wicaksono; Kartini Herlina (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
Students' Creative Problem-Solving (CPS) skills in physics require further development to prepare them for the challenges of the twenty-first century. This study aimed to examine the effectiveness of an integrated Project-Based Learning (PjBL)-STEM model incorporating Engineering Design Process (EDP) strategies and Deep Learning principles in improving senior high school students' CPS skills on the topic of Bernoulli's Principle. A quasi-experimental method with a non-equivalent control group design was employed at SMAN 1 Kalirejo. The sample consisted of two Grade 11 classes, with Class XI.F6 serving as the experimental group and Class XI.F5 as the control group. Data were collected using a two-item essay test, each comprising six sub-questions representing the six CPS indicators. The results demonstrated that the integrated PjBL-STEM model effectively enhanced students' CPS skills. The experimental group achieved an N-gain score of 0.67, substantially higher than the control group's score of 0.28. These findings were supported by the independent-samples t-test and paired-samples t-test, both of which indicated statistically significant differences (p < 0.001). The ANCOVA results further confirmed the effectiveness of the intervention (p < 0.001). Moreover, the effect size analysis yielded a partial eta squared (η²) value of 0.697, indicating a large effect of the instructional model on students' CPS skills. The improvement in CPS skills can be explained through the constructivist perspectives of Piaget and Vygotsky, which emphasize knowledge construction through experience, social interaction, and reflection. These findings are further supported by Ausubel's meaningful learning theory, as students connected the concept of Bernoulli's Principle with real-world experiences through the development of a simple insecticide project.